Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I was looking for a simple way to evaluate the integral $\int_0^\infty \frac{\sin x}{x}dx$ ( a belated look at this question). There are symmetries to be exploited, for one thing. So I had an idea, but the idea depends, optimistically, on two expressions for $\pi$ that I cannot prove, and my question is whether anyone sees reasonable proofs of either expression (1, 2 below).


$$\int_0^\infty \frac{\sin x}{x}dx = \int_0^\pi \sum_{k=0}^{k=\infty} \left\{\frac{\sin x}{x + 2 k \pi }-\frac{\sin x }{x+2k\pi+\pi}\right\} \, dx$$

The intuition behind this step is that as we make our way around the unit circle from 0 to $\pi$, for each angle $\alpha$ we have an angle $\alpha + \pi$ for which the value of $\frac{\sin x} {x}$will be smaller and negative. No need to integrate beyond $\pi$, and for angles greater than $2\pi$ we are simply dividing up the original integral's range by adding multiples of $\pi$ to the value of $x$.

WLOG we can form Riemann sums by dividing the range of integration into an even number of equi-angle subranges $dx_n$. For example, if $n = 6$, we have

$$\int_0^\pi \sum_{k=0}^{k=\infty}\sin x \left\{\frac{1}{x + 2 k \pi }-\frac{1 }{x+2k\pi+\pi}\right\} \, dx$$

$$\approx \left\{ \sum_{k=0}^\infty \sum_{n=1}^6 \sin \left( \frac{n\pi}{6}\right)\left(\frac{1}{\pi}\right) \left(\frac{1}{\frac{n}{6} + 2k}-\frac{1}{\frac{n}{6}+2k+1}\right) \right\} \left\{ \frac{\pi}{6} \right\}.$$

Taking this as true, we note that pairs of summands of the Riemann sums symmetric about $\frac{\pi}{2}$ sum to $1$, and the value of the summand at $\frac{\pi}{2}$ is $1/2$. Again, taking this as true, we have that

$$\sum f(x_n) = \frac{1}{2} + 1\cdot \frac{n-2}{2} + \sin\pi\cdot f(\pi) = \frac{n-1}{2},$$ and $$\sum f(x_n) \, dx_n = \left(\frac{n-1}{2}\right) \cdot \frac{\pi}{n}.$$

So for the approximation above for $n = 6$, we expect a value of about $\frac{5 \pi}{12}$ for high $k$.

In words, we are only counting n - 1 summands, since the last summand at $\pi$ is $0$. Since we divided the interval into $n$ subintervals, we are stuck with the sum above and the conditional limit (conditioned at least on the truth of the two limits below):

$$\int_0^\infty \frac{\sin x}{x} \, dx = \lim_{n = 1}^\infty \frac{n-1}{2}\cdot \frac{\pi}{n} = \frac{\pi}{2}.$$

The problem is this: we need to prove, to begin with, that

$$\sum_{k=0}^\infty \left(\frac{ 1}{\pi/2 + 2\pi k} - \frac{1}{\pi/2 + 2k\pi + \pi}\right) = \frac{1}{2}$$


$$ \frac{1}{\pi}\sum \frac{1}{1/2 + 2k}- \frac{1}{1/2 + 2k\pi +1}= \frac{1}{2},$$

that is,

(1) $\sum_{k=0}^\infty \frac{4}{3+16k+16k^2}= \frac{\pi}{2}$.

We must also prove for $0< j < n$ that

(2) $\sin (\frac{j\pi}{n})( \sum_{k=0}^{\infty} (\frac{ 1}{\frac{j\pi}{n} + 2\pi k} - \frac{1}{\frac{j\pi}{n} + 2k\pi + \pi}) + \sum_{k=0}^{\infty} (\frac{ 1}{\frac{(n-j)\pi}{n} + 2\pi k} - \frac{1}{\frac{(n-j)\pi}{n} + 2k\pi + \pi}))= 1$.

or , factoring $\frac{1}{ \pi}$ out of the sum and mutiplying:

$$\sin \left( \frac{j\pi}{n}\right)\left( \sum_{k=0}^\infty \left(\frac{1}{\frac{j}{n} + 2 k} - \frac{1}{\frac{j}{n} + 2k + 1}\right) + \sum_{k=0}^\infty \left( \frac{ 1}{\frac{(n-j)}{n} + 2 k} - \frac{1}{\frac{(n-j)}{n} + 2k + 1}\right)\right)= \pi.$$

(1) might be a special case of something at Wolfram's site, but I didn't spot it. (2) looks messy, but maybe induction?

If this is otherwise correct, I think one could work back from the relations for $\pi$ and establish the value of the integral. It is important not to forget that k starts at 0.

Edit: the following is equivalent to (2) and maybe easier to scan. For $0<r<1$,

$$(2) \sum_{k=0}^{\infty}\frac {2(\sin \pi r)(1+4k+4k^2-r+r^2) }{(1+2k+r)(1+2k-r)(2+2k-r)(2k+r)} = \pi$$

This was derived assuming r rational, but I don't think it matters.

share|cite|improve this question
up vote 7 down vote accepted

$$ \sum_{k=0}^N \frac{1}{\alpha + 2 k} = \frac{\Psi(N+1+\alpha/2) - \Psi(\alpha/2)}{2} $$ where $\Psi(t) = \ln(t) + O(1/t)$ as $t \to \infty$, so $$\sum_{k=0}^\infty \left(\frac{1}{1/2 + 2 k} - \frac{1}{3/2 + 2 k} \right) = \frac{\Psi(3/4) - \Psi(1/4)}{2} = \frac{\pi}{2}$$ However, I think the evaluation of $\Psi(3/4) - \Psi(1/4)$ may be just as hard as your integral.

EDIT: It turns out that $\Psi$ has the integral form $$ \Psi(t) = \int_0^\infty \left( e^{-s} - \frac{1}{(s+1)^t} \right) \frac{ds}{s}$$ so that $$ \Psi(3/4) - \Psi(1/4) = \int_0^\infty \left((s+1)^{-3/4} - (s+1)^{-1/4}\right) \frac{ds}{s} = \left. 4 \arctan((s+1)^{1/4}) \right|_0^\infty = \pi $$

share|cite|improve this answer

Another way is to decompose interval $[0,+\infty)$ into intervals of length $\frac{\pi}{2}$ instead of $\pi$ as you did. Then we'll have:

$$I = \int_0^{\frac{\pi}{2}} \sin x \cdot \left[ \frac{1}{x} + \sum_{n = 1}^{+\infty} (-1)^n \left( \frac{1}{x+n\pi} + \frac{1}{x-n\pi} \right) \right] \, dx$$ But in square bracket we have expansion of $\frac{1}{\sin x}$ into partial fractions, hence the result follows: $$I = \int_0^{\frac{\pi}{2}} dx = \frac{\pi}{2}$$

share|cite|improve this answer
@daniel I missed the link :( Ok, I'll try to make it more complete and then I'll post it there. – qoqosz Jun 26 '12 at 10:12

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.